Implementasi “7 Poe Atikan” Bagi Karakter Siswa SMP di SMPN 1 Maniis - Mochammad Candra Agustian; Risman Suryana; Sidik Nurdiansyah; Jibal Nazib; Taofik Ahmad; Irsyad Irawan; Ai Nuryati; Faiz Karim Fatkhullah (Lembaga Pengembangan Kinerja Dosen, 2026)
Character education faces significant challenges due to digital disruption and globalization that trigger moral degradation in adolescents. In Purwakarta Regency, the